Association of CEP72 rs924607 TT Genotype with Vincristine-induced Peripheral Neuropathy Measured by Motor Nerve Conduction Studies - Kavčič, Marko; Zečkanović, Aida; Jazbec, Janez; Debeljak, Marusa (Klinische Pädiatrie, 2020)
Vincristine is at the core of many treatment protocols for childhood malignancies. The major dose-limiting side effect is vincristine-induced peripheral neuropathy (VIPN) which may cause morbidity and disrupt curative treatment. Several studies have tried to identify pharmacogenetic biomarkers for susceptibility to vincristine-induced toxicity (Egbelakin A et al., Pediatr Blood Cancer 2011; 56: 361–367. Aplenc R et al., Br J Haematol 2003; 122: 240–244. Diouf B et al., JAMA 2015; 313: 815–823. Zgheib NK et al., Pharmacogenet Genomics, 2018; 28: 189–195. Gutierrez-Camino A et al., Pharmacogenet Genomics 2016; 26: 100–102. Wright GE et al., Clin Pharmacol Ther 2019; 105: 402–410. Kayilioğlu H et al., J Pediatr Hematol Oncol 2017; 39(6): 458–462). A major limitation of these studies is that VIPN is difficult to measure objectively using only clinical examination and clinical scales. This is especially true for children, who are often unable to report or grade symptoms such as paresthesia, numbness, and pain. Furthermore, some studies are questioning the validity of currently available neuropathy grading scales (Postma TJ et al., Ann Oncol 1998; 9: 739–744). Our group recently showed that electrophysiological studies can be used with great accuracy for early detection of VIPN (Kavcic M et al., J Pediatr Hematol Oncol 2017; 39: 266–271). In the previous study, we found that VIPN presents with primary axonal involvement and is more pronounced on motor neurons (Kavcic M et al., J Pediatr Hematol Oncol 2017; 39: 266–271).